Melatonin Blocks Morphine-Induced Place Preference: Involvement of GLT-1, NF-κB, BDNF, and CREB in the Nucleus Accumbens - Alghamdi, Badrah S.; Alshehri, Fahad S. (Frontiers in Behavioral Neuroscience, 2021)
Opioid addiction remains a widespread issue despite continuous attempts by the FDA to help maintain abstinence. Melatonin is a neurohormone considered to be involved only in the neuroendocrine and reproductive systems; however, recent reports have demonstrated its potential to attenuate drug addiction and dependence. Cumulative studies have suggested that melatonin can attenuate the rewarding effects of several drugs of abuse, including opioids. This study aimed to investigate the effect of melatonin (50 mg/kg) on morphine (5 mg/kg) to produce place preference. As well, investigated the effect of melatonin and morphine on the expression of GLT-1, BDNF, NF-kB, and CREB within the nucleus accumbens. Male Wistar rats were divided into control, morphine, melatonin, and morphine + melatonin groups. The study involved a two-phase habituation phase from day 1 to day 3 and an acquisition phase from day 5 to day 14. The CPP score, distance traveled, resting time, ambulatory count, and total activity count were measured for all animals. Rats that received morphine showed a significant increase in CPP score compared to those in the control group. Morphine treatment reduced the mRNA expression of GLT-1, BDNF, and CREB and increased that of NF-kB. However, melatonin treatment administered 30 min before morphine treatment attenuated morphine place preference and reversed GLT-1, BDNF, NF-kB, and CREB expression levels. In conclusion, the study results indicate, for the first time, the new potential targets of melatonin in modulating morphine-induced CPP.